La índole de un instituto de vida consagrada como núcleo de su carisma. Comentario al can. 578 del Código de Derecho Canónico - Aspe LC, Roberto (Alpha Omega, 2013)
In this article, the author systematically addresses the topic of charism, seeking to present the conceptual content of an institute of consecrated life’s patrimony according to canon 578 of the Code of Canon Law. In particular, he presents the character of the institute as the basis of the charism, that is, as the nucleus or essence which best reflects the charism in the life of the institute. The character, in this sense, is considered as the unity that comes from the combination of proper and particular elements that the charism imprints on the new community and which give it an individual identity that differentiates it from other similar communities of the same species in the Church. The character also involves a particular style of sanctification and apostolate that establishes a tradition specific to the institute, in such a way that its objective elements are sufficiently identifiable. From this perspective, healthy traditions come from the character of the institute; they show how the charism is “incarnated” in its members in a way that corresponds to their vocation. This is why the Church defends and sustains the proper character of institutes and proposes it as a criterion for renewal (cfr. LG, 44; MR, 11). The character, thus understood, will be the element of the patrimony which most reflects the charism, as well as being the factor that will determine the nature, purpose and spirit of each institute.